Isolation and Chemical Investigation of Bioactive Metabolites from a Sclerophytum Species of the Indian Ocean - Mathrusri Annapurna, M. (Asian Journal of Chemistry, 2010)
A soft coral, which was found in abundance, was collected during December 1986 on the coasts of Andaman and Nicobar islands of the Indian Ocean. The specimen was identified up to the genus level as Sclerophytum by Zoological Survey of India. The isolation and characterization of the compounds was done in which a compound ethyl arachidonate was structurally elucidated.